2022
DOI: 10.1016/j.meegid.2022.105206
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of TMPRSS2 rs2070788 polymorphism with COVID-19 case fatality rate among Indian populations

Abstract: SARS-CoV-2, the causative agent for COVID-19, an ongoing pandemic, engages the ACE2 receptor to enter the host cell through S protein priming by a serine protease, TMPRSS2 . Variation in the TMPRSS2 gene may account for the disparity in disease susceptibility between populations. Therefore, in the present study, we have used next-generation sequencing (NGS) data of world populations from 393 individuals and analyzed the TMPRSS2 gene using a haplotype-based approach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Interestingly, our study identified the G allele of the TMPRSS2 rs2070788 to be associated with the presence of post-COVID dyspnea. These results agree with previous findings showing that pulmonary TMPRSS2 expression is higher in people with GG genotype as compared to the AG and AA genotypes [ 36 ]. It is possible that some polymorphisms can be associated with specific post-COVID symptoms or that the effect of the investigated polymorphisms could induce a more severe COVID-19 phenotype, indirectly affecting the development of particular post-COVID symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, our study identified the G allele of the TMPRSS2 rs2070788 to be associated with the presence of post-COVID dyspnea. These results agree with previous findings showing that pulmonary TMPRSS2 expression is higher in people with GG genotype as compared to the AG and AA genotypes [ 36 ]. It is possible that some polymorphisms can be associated with specific post-COVID symptoms or that the effect of the investigated polymorphisms could induce a more severe COVID-19 phenotype, indirectly affecting the development of particular post-COVID symptoms.…”
Section: Discussionsupporting
confidence: 93%
“… ( Rahimi et al, 2021 ) TMPRSS2 rs2070788 India 393 COVID-19 patients rs2070788 may lead to worse clinical outcomes in COVID-19 patients. ( Pandey et al, 2022 ) TIRAP rs8177374 Netherlands 116 COVID-19 patients Carriers of rs8177374 could be associated with a significantly lower COVID-19 mortality. ( Traets et al, 2022 ) TMPRSS2 rs17854725/rs75603675/rs12329760/rs4303795 Iran 288 COVID-19 patients These polymorphisms were associated with increased risk of COVID-19 infection and severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, most of these association studies were conducted in European and East Asian cohorts, with a very few studies in South Asian cohorts (Srivastava et al 2020b ; Pandey et al 2022 ; Srivastava 2020a ; Ahmad et al 2021 ). This highlights the necessity of conducting more association studies in increasingly diverse populations.…”
Section: Non-hla Genetic Findings In Covid-19mentioning
confidence: 99%